Kesesuaian Video di Kanal YouTube Learn German with Anja sebagai Media Pembelajaran Keterampilan Berbicara Bahasa Jerman Kelas XI Semester Genap - Widyadhana, Evania; Titaley, Audrey Gabriella (LATERNE, 2024)
Language is a very important thing for humans because language is a bridge to connect with many people. SMA Negeri 12 Surabaya have a German language subject. However, students in grade XI at SMA Negeri 12 Surabaya have difficulty in speaking German. Therefore, the problem formulation and the purpose of this study is how much the level of suitability of videos on the YouTube channel Learn German with Anja theme Essen und Trinken with the learning objectives of German language material class XI semester 2 at SMAN 12 Surabaya. The data sources of this research are 14 videos from the YouTube channel Learn German with Anja theme Essen und Trinken. Based on the results of the analysis, it was found that of the fourteen videos analyzed, 3 videos reached 82%-84% and were categorized as very suitable for use as a medium for learning German in grade XI theme Essen und Trinken. These three videos align with Teaching Points (TP) 1, 2, 3, and 4 in the German language module for grade XI, theme Essen und Trinken.